2016
DOI: 10.1016/j.celrep.2016.01.052
|View full text |Cite
|
Sign up to set email alerts
|

C. elegans Body Cavity Neurons Are Homeostatic Sensors that Integrate Fluctuations in Oxygen Availability and Internal Nutrient Reserves

Abstract: SUMMARY It is known that internal physiological state, or interoception, influences central nervous system function and behavior. However, the neurons and mechanisms that integrate sensory information with internal physiological state remain largely unknown. Here, we identify C. elegans body cavity neurons called URX(L/R) as central homeostatic sensors that integrate fluctuations in oxygen availability, with internal metabolic state. We show that depletion of internal body fat reserves increases the tonic acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
67
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(73 citation statements)
references
References 48 publications
(65 reference statements)
5
67
0
Order By: Relevance
“…This would be a potential means of anticipating starvation that would enable animals to rapidly relocate to more optimal environments. Given that C. elegans lose approximately 70% of their body fat within 2-3 h of fasting (40), the rapid reversal of exploratory behavior is an important survival mechanism in these animals.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This would be a potential means of anticipating starvation that would enable animals to rapidly relocate to more optimal environments. Given that C. elegans lose approximately 70% of their body fat within 2-3 h of fasting (40), the rapid reversal of exploratory behavior is an important survival mechanism in these animals.…”
Section: Discussionmentioning
confidence: 99%
“…To more directly investigate whether increased fat storage in ets-5 mutant animals causes reduced exploration, we decreased body fat levels in the intestine by RNAi of pod-2 (encoding an acetyl-CoA carboxylase that produces malonyl CoA, a crucial precursor of fatty acid synthesis) and elo-2 (encoding a palmitic acid elongase that converts C16:0 fatty acids to C18:0 fatty acids) (39)(40)(41). We found that pod-2 and elo-2 RNAi partially suppressed In addition, the exploratory defect of ets-5(tm1734) mutant animals is fully suppressed when animals are grown on this inedible food source.…”
Section: Malnutrition Suppresses Exploration Defects Caused By Loss Omentioning
confidence: 99%
“…Given their unique anatomic position, these neurons are hypothesized to mediate bidirectional communication between nervous system and peripheral tissues as they have the capacity to both release and detect circulating signals. Interestingly, neural serotonin signaling is thought to promote intestinal fat metabolism through the release of an neuroendocrine signal from URX neurons [31,32] and fluctuations in peripheral fat metabolism modulate the tonic activity of URX [102]. We find that targeted expression of egl-2(gf) in only the body cavity neurons is sufficient to block the feeding increasing effects of serotonin and mimic the effects of loss of acox-1 ( Figure 7B).…”
Section: Acox-1 Regulates Urx Body Cavity Neuron Activity To Limit Fementioning
confidence: 86%
“…To directly assess the effects of ACOX-1 activity on body cavity neuron function, we measured intracellular Ca 2+ transients from the URX body cavity neurons using the genetically-encoded calcium reporter GCaMP5K [102,104]. We selected URX neurons as calcium dynamics from these cells have been well documented and intriguingly their activity has recently been shown to be modulated by internal metabolic cues and starvation [102,[105][106][107]. URX neurons play a well-documented role in oxygen sensing and are robustly and rapidly activated under atmospheric conditions (21% oxygen) ( Figure 8A and 8C) [105,[108][109][110].…”
Section: Acox-1 Regulates Urx Body Cavity Neuron Activity To Limit Fementioning
confidence: 99%
“…Our script used animal centroid coordinate data to determine mean population headings (imported from Image-Pro Plus, see above). Worm responses to diverse stimuli change over time based on their internal state (Gosh et al, 2016;Witham et al, 2016;Klein et al, 2017). To compare animals in similar states, we binned each animal track into 5% intervals for each trajectory in order to normalize headings for animals that completed the same proportion of their total trajectory.…”
Section: Animal Directional Headingsmentioning
confidence: 99%